The Role of the School Principal as a Manager in the Implementation of P5 in the Merdeka Curriculum at SD Negeri 2 Sanggrahan, Kranggan District - Sofiana, Nur Mei Laidatul; Yuliejantiningsih, Yovitha; Maryanto, Maryanto (Jayapangus Press, 2025)
This study aims to analyze the role of the school principal as a manager in the implementation of the Pancasila Student Profile Strengthening Project (P5) within the Merdeka Curriculum at SD Negeri 2 Sanggrahan, Kranggan District, Temanggung Regency. This research uses a descriptive qualitative approach with data collection through interviews, observations, and documentation. The obtained data were analyzed using thematic analysis techniques to gain an in-depth understanding of the implementation of P5 and the role of the principal in managing the curriculum. The results of the study show that SD Negeri 2 Sanggrahan has successfully implemented the Merdeka Curriculum, although it is not a model school, with a focus on the development of student character through the dimensions of the Pancasila Student Profile such as independence, cooperation, critical thinking, and creativity. The role of the school principal as a manager is crucial in ensuring the success of this program, with structured steps in the planning, organizing, and supervising the implementation of P5. The principal also plays a key role as an instructional leader who fosters collaboration among teachers, students, parents, and the community in supporting the implementation of this character-based project. However, challenges related to limited infrastructure and less-than-optimal community involvement still need to be addressed. This study recommends enhancing technology facilities, strengthening critical and creative thinking dimensions among students, and improving teacher competencies through continuous training. Furthermore, the involvement of parents and the community in supporting the implementation of P5 should be increased through more intensive socialization. Thus, it is expected that SD Negeri 2 Sanggrahan will continue to develop as an effective school in implementing the Merdeka Curriculum and serve as a model for other schools in fostering student character and academic competence holistically.